ET VILDNIS AF TABUER: Jagten på en kulinarisk struktur - Liep, John (Tidsskriftet Antropologi, 1998)
John Liep: A Wilderness of Taboos: The Quest for a Culinary Structure Recent anthropological research in Melanesia has focused on the construction of the person, theories of conception and procreation, and flows of substances through social relations and persons. There will often be a correspondence between substances such as sperm and biood, bodily parts such as bone and flesh, and contrasting foods that are gendered. An asymmetric constitution of the person and a clear structuration of food prestations between affinal sides may exist. A study of these themes on Rossel Island, Papua New Guinea yielded frustrating results. No clear idea of contrasting, gendered body aspects was found. Further, a large number of food taboos for menstruating, pregnant and lactating women was distributed in clusters that were amenable to various logics of interpretation without any total structural logic appearing. This negative result is explained by the absence of any sustained practice of asymmetric marriage and corresponding complementary prestations between affines, which would reproduce an ordering asymmetric structure of the person and of the universe of foods.